Experience of Vacuum-Assisted Closure in the Surgical Treatment of Malignant Skin Tumors after Skin Grafting - Korovin, Sergii; Ostafiichuk, Vasyl; Diedkov, Serhii; Kukushkina, Mariia (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Skin grafts may be used to reconstruct large skin defects after the excision of malignant skin tumors. Vacuum-assisted closure (VAC) leads closer approximation of the free flap. AIM: The objective of this study was to estimate the engraftment of grafts using VAC and explore factors influencing this process. MATERIALS AND METHODS: This study included 31 patients with skin cancers after a wide tumor excision. The wound defects were closed using a split-thickness skin graft and the VAC dressing. RESULTS: Complete and partial engraftment was observed in 17 (54.8 %) and 14 (45.2%) cases, respectively. The mean area of the wound defects among patients with complete engraftment was 24.3 ± 20.6 cm2, while that of the group with partial engraftments was 56.5 ± 58.8 cm2 (p = 0.0017). In the complete engraftment group, the average number of days with the VAC dressing was 7.2 ± 0.44 days, versus 6.9 ± 0.27 days in the partial engraftment group (p = 0.032). CONCLUSION: VAC dressing after skin grafting in the surgical management of malignant skin tumors provided good results. The area of the wound defect and the average number of days with VAC dressing is significant factors influencing the outcomes of skin grafting.